2021
DOI: 10.1007/s00394-021-02569-1
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to a healthy Nordic diet and risk of type 2 diabetes among men: the Kuopio Ischaemic Heart Disease Risk Factor Study

Abstract: Purpose To investigate the association between healthy Nordic diet and risk of type 2 diabetes (T2D) in middle-aged and older men from eastern Finland. Methods A total of 2332 men aged 42–60 years and free of T2D at baseline in 1984–1989 were included. Diet was assessed with 4-day food records at baseline and the healthy Nordic diet score was calculated based on a modified Baltic Sea Diet Score. T2D diagnosis was based on self-administered questionnaires, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…Whole grains, a typical food in the NND, showed a likely protective effect against the development of T2D [144]. A recent study in middle-aged and older men from eastern Finland (n = 2332; aged 42-60 years) free of T2D at baseline reported that after an average follow-up of 19.3 years the lowest vs. the highest quartile of adherence to NND was associated with a higher risk of incident T2D and with a higher blood glucose and insulin concentrations after adjustment for confounders [152]. In the same cohort, participants with higher adherence to NND exhibited a 9% reduced incidence of colorectal cancer (CRC) [153].…”
Section: Nordic Dietmentioning
confidence: 99%
See 1 more Smart Citation
“…Whole grains, a typical food in the NND, showed a likely protective effect against the development of T2D [144]. A recent study in middle-aged and older men from eastern Finland (n = 2332; aged 42-60 years) free of T2D at baseline reported that after an average follow-up of 19.3 years the lowest vs. the highest quartile of adherence to NND was associated with a higher risk of incident T2D and with a higher blood glucose and insulin concentrations after adjustment for confounders [152]. In the same cohort, participants with higher adherence to NND exhibited a 9% reduced incidence of colorectal cancer (CRC) [153].…”
Section: Nordic Dietmentioning
confidence: 99%
“…The key messages underlying the NND guidelines are the following: (1) including more calories from plant-based foods and less from meat; (2) use of more foods coming from the lakes and sea (comprising seaweeds and shellfish); and (3) including more wild local foods from the countryside (plants, berries, mushrooms, and aromatic herbs) [142]. Although NND has been developed in recent times, the literature on this healthy dietary pattern has grown, showing significant associations between NND and several health outcomes including various NCDs (i.e., CVD, obesity, some types of cancer, neurodegenerative diseases) and mortality [59,141,[144][145][146][147][148][149][150][151][152][153][154][155][156][157][158][159], thus increasing overall life and health expectancies.…”
Section: Nordic Dietmentioning
confidence: 99%
“…To our knowledge, this research represents the rst evaluation of the relationship between adherence to BSDS and HNFI and odds of ARC. Although higher adherence to BSDS and HNFI has been reported to modify risk of some noncommunicable in ammatory related diseases including diabetes (24,25), cancers (16, 26) and CVD (27,28), unequivocal epidemiological evidence on the relationship between BSDS and HNFI or their components and odds of ARC remains elusive. Previously observational studies have shown that a higher BSDS score is associated with greater life satisfaction in older adults (29), lower circulating in ammatory markers including hs-CRP (30) and abdominal obesity (31), while higher compliance with a modi ed Nordic diet has been proposed to improve low-grade in ammation (32), weight management (33), and hypo-metabolic state in overweight and obese women (34).…”
Section: Discussionmentioning
confidence: 99%
“…HNFI was created by Olsen et al ( 18) and includes only 6 foods with the health bene ts of a traditional Nordic diet including whole-grain bread, apples and pears, cabbages, sh, barley, and root vegetables, whereas BSDS was designed to demonstrate adherence to the healthy Nordic diet based on foods commonly cultivated in the Nordic counters and includes fruits and berries, vegetables, low-fat milk, cereals, meat products, alcohol, total fat and fat ratio (19). Although, to date no study has investigated the association between BSDS and HNFI and risk of any type of cataract, but a signi cant negative association between adherence to Nordic dietary pattern and risk of diabetes (20) and abdominal obesity (21), which were previously purported to be potential risk factors for ARC (8, 22), was reported in recent studies. Owing to the high amount of antioxidant rich foods in Nordic diet pattern and easy availability of these food items in Iran, we conducted this study to clarify whether adherence to a HNFI and BSDS may reduce risk of ARC.…”
Section: Introductionmentioning
confidence: 99%
“…The Nordic diet, based on typical Finnish foods ( 31 ), shares nutritional recommendations with the Mediterranean diet: both emphasize local seasonal foods and promote sustainability and preservation of the environment; their main difference is the type of oil used for cooking, where the Nordic diet preferably uses canola oil. In relation to the Nordic diet, epidemiological studies are still lacking to demonstrate its effects on health, as shown with the Mediterranean diet ( 32 ).…”
Section: Introductionmentioning
confidence: 99%